Perceived stress and sleep quality among university students in the San Martin region, Peru - Gavidia, Rafaela (2025)
Perceived stress and sleep disturbances constitute frequent problems among the university population due to the academic and personal demands inherent to this stage of life. In this context, the purpose of this research was to determine the relationship between the level of perceived stress and sleep quality among university students. The study was conducted using a quantitative approach, with a basic scope, a descriptive-correlational level, and a non-experimental cross-sectional design. The population consisted of 525 university students from public and private universities in the San Martín region. The results showed the existence of a significant relationship between perceived stress and sleep quality, highlighting the association between eustress and insomnia, as well as between distress and insomnia (r = -0.025 and r = 0.341; p < 0.05). In conclusion, it was determined that higher levels of perceived stress are associated with higher levels of insomnia, which negatively affects the sleep quality of university students.